Alteraciones electrolíticas como predictores de severidad en gestantes con preeclampsia del Hospital Regional de Loreto - Atachagua Carrillo, Nesias Marsoline (2022)
The present study will be carried out with the purpose of identifying electrolyte alterations as predictors of severity in pregnant women with preeclampsia. Pregnant women treated at the Obstetrics Service of the Loreto Regional Hospital evaluated during the period 2018 - 2020 will be included. a sectional, cross-sectional, analytical, observational design. The OR will be obtained for electrolyte alterations in terms of its association with severity in preeclampsia, if this is greater than 1, the 95% confidence interval will be calculated. Multivariate analysis will be performed with logistic regression for intervening variables.